THE EFFECTIVENESS OF FISCAL INCENTIVE POLICY IN BONDED ZONES - Firmansyah, Vahri; Pratiwi, Ratih (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
One of the government’s efforts toward National Economic Recovery from the pandemic is to urge exports by giving fiscal incentives to companies in Bonded Zones. The companies given this facilitation have to commit themselves to growing the economy. This study aims to provide empirical evidence related to the effect of fiscal incentives in the form of suspension of customs duty and exchange rate, on exports. This is a quantitative study using multiple linear regression analysis using secondary data of 4 companies in Bonded Zones under Regional Office of the Directorate General of Customs and Excise, East Kalimantan between January 2019 and December 2021. The results show that fiscal facilitation has a positive and significant effect on exports value, whereas Rupiah exchange rate does not have any significant effect. This supports the government’s effort in providing fiscal facilitation to companies in Bonded Zones by showing that it increases exports.